Does Artificial Intelligence Affect Actual Learning Experience Among University Students? - Agit, Alamsyah; Muharram, Susilawati; Mujahidin (IJER (Indonesian Journal of Educational Research), 2023)
Development of technology has been rapidly increased, in general, most technology has been able to assist humans in any way, from industry workers to academicians, the role of technology can be seen everywhere nowadays. One of these common technologies can be seen in academic field, which is an artificial intelligence, which has the purpose to provide scientific information as the user requested. However, this form of technology, despite providing very useful information, also has the potential to provide false sources. Despite this, many university students have learned the way to use this form of technology, which has the potential to weaken, and decrease their creativity in thinking, moreover, in writing. Further, this form of technology can hinder the actual learning experience students can have during their college years. This paper serves the purposes to explore the use of AI in university, using qualitative methods, and deductive reasoning, this paper will use empirical research and data, as its main source of material, from this information, this paper will provide result, and findings, that are relevant to the theme of this paper. The result of this paper, indicate that, even though technology may have provided convenience among students, the lecturer has cautious toward this change, and provide a correct way to use AI, this method has strengthened the ability of the students to use AI more correctly, which gives them ability to use AI to their advantage without hindering learning experience.